An exploration into self-extending systems in early literacy in English of Grade One isiXhosa speaking learners - O'Donoghue, Elizabeth Lindsay (Rhodes University, Faculty of Education, Department of Education, 2012)
The purpose of this research was to explore the ways in which a small, purposefully sampled group of Grade One isiXhosa-speaking children began the process of becoming literate in English as their second language. The research looked specifically for evidence of strategic behaviours in reading and writing which, according to Clay (200 I, 2005), form the foundation for self-extending systems and have the potential to accelerate learning. The research was guided by the principles of Clay's early intervention Reading and Writing Recovery. By Clay's definition, self-extending systems are literacy processing systems that work, that is, they enable children to continue to learn to read by reading and to write by writing. Within this context, the research explored the role of oral language in learning to read and write in English. Consideration was given to the potential for transfer of the principles that underlie Reading Recovery to South African mainstream classrooms in an attempt to raise literacy outcomes for all. This is a particularly urgent need in South Africa where many attempts to tum around poor trajectories of literacy learning do not seem to have the desired long term effects. The results of the research showed that the children began to actively engage in their English literacy learning within a network of strategies, primarily motivated by making meaning of their texts. The findings of the research suggested that a mismatch of needs and instructional procedures was evident here in this formative stage of second language literacy learning. The results suggested that children who were already educationally at risk for a multitude of reasons, were being set back even further by instructional approaches that were unresponsive to their linguistic needs.
Keywords: English language -- Study and teaching (Elementary) -- Foreign speakers -- South Africa -- Eastern Cape; Second language acquisition -- South Africa -- Eastern Cape; Second language acquisition -- Ability testing -- South Africa -- Eastern Cape; Language and languages -- Study and teaching (Secondary) -- Foreign speakers -- South Africa -- Eastern Cape; Competence and performance (Linguistics) -- South Africa -- Eastern Cape; Literacy -- Study and teaching (Elementary) -- South Africa -- Eastern Cape; Reading (Elementary) -- South Africa -- Eastern Cape; Children -- Writing -- Study and teaching (Elementary) -- South Africa -- Eastern Cape; Reading Recovery®